Stereological study on organelle distribution in human oocytes at metaphase-I - Coelho, Sofia Peres (2020)
The ultrastructure of metaphase-I (MI) human immature oocytes is largely unreported. Which organelles are more frequent and their location are questions without a comprehensive answer. The aim of this dissertation is to describe the ultrastructure of MI human oocytes, qualitatively by describing their morphology, and quantitatively, using stereological analysis to analyse the relative volumes (Vv) of each organelle and their distribution. Moreover, the quantitative analysis of organelles in MI oocytes is compared to prophase-I oocytes, quantitatively analysed in a previous study. MI oocytes, retrieved after ovarian stimulation, were processed for transmission electron microscopy, serially sliced and photographed. Stereological analysis using a classical manual stereological technique based on point-counting was performed to compute relative volumes occupied by each organelle. Kruskal-Wallis test and Mann-Whitney U-test (with Bonferroni correction) were used to compare Vv occupied by organelles in the entire oocyte and three oocyte regions – cortex, subcortex and inner ooplasm. Mitochondria and smooth endoplasmic reticulum (SER) elements are the organelles with highest Vv in the entire oocyte and each oocyte region. No significant differences were detected in Vv of mitochondria and SER tubules, tubular aggregates, small vesicles and medium vesicles among oocyte regions. SER large vesicles show significant higher Vv (P = 0.011) in the inner ooplasm than in the subcortex (0.2% vs 0%). Conversely, cortical vesicles present significant higher Vv (P = 0.004) in the cortex than in the subcortex (0.96% vs 0.1%) and inner ooplasm (0.96% vs 0.1%); and vesicles with dense granular contents present significant higher Vv (P = 0.005) in the cortex than in the subcortex (0.1% vs 0%). No significant differences were observed in Vv of dictyosomes and lysosomes. These descriptive and quantitative data, combined with similar analysis of metaphase-II human oocytes and molecular approaches, could contribute to the improvement of stimulation protocols and in-vitro maturation methods.